(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A total of 225 native Hilly chickens (152 females and 73 males) were reared in colony cages as large, medium and small body size groups for 10 months period to compare their production performances. The mean body weights of adult female and male birds were 2129, 1786 and 1457g; and 2436, 2834 and 2249 g respectively. The age of first egg were 158, 147 and 140 days and hen-day egg production were 44.56 ± 0.5, 46.15 ± 0.5 and 48.84 ± 0.7 percent (P<0.01) respectively. The average egg weight were 43.05 ± 0.1, 42.87 ± 0.1 and 41.79 ± 0.24 (P<0.01). The average per bird per day feed consumption was 105, 107 and 105g (P<0.01) and mortality was 6.2, 5.1 and 11.1 percent respectively. The average hatchability percentage performed by 14 broody hens reared on litter floor was 65.71 and the average hatching egg weight and chick weight was 45.9 and 31.7 g respectively. Broodiness character of hilly chicken rearing in cage system was rarely observed. It may be concluded that locally collected large size Hilly chicken has potentiality to be used as meat type chicken. It may be suggested that hilly chicken can be improved further through new collection of local hilly birds to undertake conservation and improvement programme. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 152-155